Writing Anxiety, Knowledge of and Attitude to Yoruba Orthography as Correlates of Secondary Students’ Achievements in Yoruba Essay Writing - Akinsola, Ifeoluwa Theophilus; Osundiran, Ebunoluwa Esther (FKIP - Universitas Riau, 2024)
This study investigated secondary students’ writing anxiety, attitude to and knowledge of Yoruba orthography as indicators of their achievement in Yoruba essay writing in the Ibadan metropolis, Oyo State. Three research questions were answered using the survey research design of the correlational type. Four hundred and twenty (420) Senior Secondary II students taking Yoruba in 12 purposively selected secondary schools in Ibadan metropolis responded to the four self-constructed instruments used. Data collected were analysed using the Pearson’s Product Moment of Correlation (PPMC) and Multiple Regression Analysis at 0.05 level of significance. Writing anxiety (r = .125; p<0.05) and knowledge of Yoruba orthography (r = .147; p<0.05) had significant positive relationship with students’ achievement in Yoruba essay writing while attitude to Yoruba orthography (r = .084; p>0.05) had positive but non-significant relationship with students’ achievement in Yoruba essay writing. The joint contribution of the three independent variables was significant (F (3; 407) = 4.848; Adj. R2 = .027; p = .003<0.05). However, the knowledge of Yoruba orthography (Beta = .136; p=.006<0.05) is the factor that had significant relative contribution to students’ achievement in Yoruba essay writing. Therefore, students should endeavor to develop interest in and increase their knowledge of Yoruba orthography.